Investigating the Aquatic weeds on the Westlake Wetland: Detrimental effects and management options - Archibald, Sally (Department of Biological Sciences, 2017)
The aquatic weeds on the Westlake wetland at Zandvlei (Cape Town, South Africa) were investigated in terms of their detrimental effects, and the biotic and abiotic conditions associated with their nuisance growth. Eichhornia crassipes was the most problematic of the weeds, both from a human perspective and in its effect on the system, and it appears to out-compete the initially more abundant Ceratophyllum demersum and Azolla filiculoides after disturbances such as clearing and flooding. Temperature, current strength and inter-species interactions were controlling the distribution and growth of the weeds on a seasonal scale, but over the long term it is likely that lower salinities, together with high concentrations of nitrogen and phosphorus, have caused the increased growth noticeable over the last fifteen years. The present management programme of annual mechanical clearance seems to be the most cost-efficient, ecosystem-friendly option but it is suggested that the possibility of increasing the salinity in the wetland be investigated as a way of slowing the regrowth of the weeds after clearance.